Practicum teachers' perception on bullying in Malaysian schools / Ilman Nazhifi Raflee - Raflee, Ilman Nazhifi (Faculty of Education, 2014)
This study investigated praeticum teachers’ perception on bullying, how serious bullying is, who are the bullies and being bullied, why is someone being bullied and how bullying can be prevented. Questionnaires were distributed among 30 practicum teachers who had gone through their praeticum in the previous semester. Data was tabulated using frequencies and descriptive analyses. It was found that bullying is perceived to be a serious matter in Malaysian secondary schools. Based on the data, bullying can happen in various acts such as social isolation, teased, degraded, giving rude gestures and et cetera. The data also showed bullying can happen anywhere in the school, especially in the classroom and gym. This study proves that the bullies are mostly students who are very close to the victims, namely their own classmates. Various reasons such as jealousy, craving for power and seeking attention are some factors that triggers bullying among students. Teachers, school personnel, parents and the students themselves play an important role of preventing bullying in school.